The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1177/10812865211031278
|View full text |Cite
|
Sign up to set email alerts
|

Free vibration analysis of nonlocal nanobeams: a comparison of the one-dimensional nonlocal integral Timoshenko beam theory with the two-dimensional nonlocal integral elasticity theory

Abstract: Beam theories such as the Timoshenko beam theory are in agreement with the elasticity theory. However, due to the different nonlocal averaging processes, they are expected to yield different results in their nonlocal forms. In the present work, the free vibration behavior of nonlocal nanobeams is studied using the nonlocal integral Timoshenko beam theory (NITBT) and two-dimensional nonlocal integral elasticity theory (2D-NIET) with different kernels and their results are compared. A new kernel, termed the comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 96 publications
0
4
0
Order By: Relevance
“…Danesh and Javanbakht investigated the free vibration behavior of nonlocal nanobeams using the nonlocal Timoshenko beam theory and two-dimensional nonlocal integral elasticity theory. They found that the natural frequencies obtained from the two-dimensional nonlocal integral elasticity theory were comparable with those obtained from the nonlocal Timoshenko beam theory for any boundary condition [43].…”
Section: Introductionmentioning
confidence: 69%
“…Danesh and Javanbakht investigated the free vibration behavior of nonlocal nanobeams using the nonlocal Timoshenko beam theory and two-dimensional nonlocal integral elasticity theory. They found that the natural frequencies obtained from the two-dimensional nonlocal integral elasticity theory were comparable with those obtained from the nonlocal Timoshenko beam theory for any boundary condition [43].…”
Section: Introductionmentioning
confidence: 69%
“…where p i , τ 1 ijk and m s ij are the work conjugate of γ i , η 1 ijk and χ s ij , respectively. We note that there are several possible formulations available in literature [22,27,[46][47][48][49][50].…”
Section: Representation Of Gradient Effects In Terms Of Length Scale ...mentioning
confidence: 99%
“…These include nonlocal elasticity theory [16][17][18][19][20], micropolar [21][22][23], strain gradient theory [24][25][26], surface elasticity theory [27,28]and modified couple stress theory [29][30][31][32][33]. Based on the aforementioned theories, significant attention has been dedicated to studying the mechanical behavior of Micro/Nano Structures, particularly in the context of bending [34][35][36], buckling [13,37,38], vibration [39][40][41][42], and wave propagation [43][44][45][46]. Among these studies, particular attention has been given to examining the free vibration behavior of nanoscale structures.…”
Section: Introductionmentioning
confidence: 99%